On an analytical solution for the two energy group neutron space-kinetic equation in heterogeneous cylindrical geometry. (November 2019) - Oliveira, F.R.; Fernandes, J.C.L.; Bodmann, B.E.J.; Vilhena, M.T.
Highlights: The work propose a new way to calculus neutron kinetic spatial problem that is completely analitics. The fluxes in cylindrical coordinates are investigated and solved for the problem. The work include more energy groups and neutrons precursors in compare with others works in the literature. Abstract: The present work is a continuation for the multigroup scalar neutron flux and multigroup precursor concentration model, here two energy groups and one delayed neutron precursor concentration. We determine a general solution for this problem considering cylinder geometry. The solution is determined using variable separation. The complete spectrum is analysed with respect to each variable separation and truncated such as to allow a parametrisation of the solution for the considered homogeneous problem. For a specific choice of nuclear parameter we present the three dimensional solution for the fast, the thermal angular neutron fluxes and the delayed neutron precursor concentration. Possible extensions of the model and solutions are indicated.